2015
DOI: 10.1111/ggi.12616
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the barriers affecting medication adherence in older adults

Abstract: Medication adherence is a crucial part in the management of chronic diseases. As older adults form a greater proportion of the population with chronic diseases and multiple morbidities, understanding medication adherence in older adults becomes important. In the present article, we aimed to systematically review the literature for the factors associated with medication adherence in the geriatric population. We carried out a literature search using electronic databases and related keywords. 17 391 articles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(212 citation statements)
references
References 70 publications
(275 reference statements)
5
170
0
13
Order By: Relevance
“…The keywords used in the search strategy were obtained from several previous systematic reviews in the field of medication adherence . The search strategy was based on two queries that were combined together to perform the search.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The keywords used in the search strategy were obtained from several previous systematic reviews in the field of medication adherence . The search strategy was based on two queries that were combined together to perform the search.…”
Section: Methodsmentioning
confidence: 99%
“…The keywords used in the search strategy were obtained from several previous systematic reviews in the field of medication adherence. [21][22][23][24] The search strategy was based on two queries that were combined together to perform the search. The first search query was based on the title search using phrases such as 'medication adherence' or 'adherence to medication'.…”
Section: Search Strategymentioning
confidence: 99%
“…7 Further, medication nonadherence, along with suboptimal prescribing and drug administration, results in $290 billion in avoidable medical spending annually in the United States. 8 Older adults, aged 65 years or older, with multiple chronic conditions face medication nonadherence, 9,10 and such nonadherence is associated with potentially avoidable health services use. 8,11 For example, previous studies found that medication adherence rates among patients with at least one chronic condition can be as low as 50%, 12,13 and nearly 15% of chronically ill Americans specifically stated that costs were the main reason for medication underuse.…”
mentioning
confidence: 99%
“…In terms of thinking about how an SMS-based system could be optimized to address medication nonadherence, it may be helpful to consider the problem in the context of the framework proposed in the systematic review by Yap et al [11] on the barriers to medication adherence in older adults, in which they organize the reasons for nonadherence that have been proven to date into 5 categories: patient factors, medication factors, physician factors, system-based factors, and other factors. Many of the factors they identified include situations and patient beliefs that could conceivably be identified and addressed by an SMS- or phone call–based system (see Textbox 1).…”
Section: Introductionmentioning
confidence: 99%
“…Given that Yap et al [11] identified 80 different factors shown to influence nonadherence, it seems clear that this problem is complex and multifactorial. While forgetfulness is often cited as a reason for medication nonadherence, Saberi et al [10] found that interventions relying solely on reminding HIV patients to take their antiretroviral therapy were largely not effective, leading them to speculate that the attributed forgetfulness was a simple excuse for more complex underlying reasons like stigma, depression, drug abuse, and lack of social support.…”
Section: Introductionmentioning
confidence: 99%